An Introduction to Religion and Religious Themes in Rock Music - Olson, Carl. (Lewiston : Edwin Mellen Press, 2011)
Olson produces a case study in creative pedagogy that incorporates popular culture into religious studies. Utilizing rock music to discuss religious themes provides a new and unique approach to theological topics. The book does not only focus on overtly religious rock music but rather posits that lyrical usage of themes by rock musicians over the years has inevitably come across themes from world religions sometimes even unbeknownst to themselves
Description based upon print version of record.
Keywords: Asia, Central -- Religion; Rock music -- Religious aspects; LITERARY CRITICISM / General; TRAVEL / Special Interest / Literary; Electronic books